Investigation of the stemness and wound-healing potential of long-term cryopreserved stromal vascular fraction cells - Naoki Inafuku; Yoshihiro Sowa; Tsunao Kishida; Seiji Sawai; Edward Hosea Ntege; Toshiaki Numajiri; Kenta Yamamoto; Yusuke Shimizu; Osam Mazda (Regenerative Therapy)
Introduction: Stromal vascular fraction (SVF), a heterogeneous cell population primarily derived from adipose tissue, is widely utilized in regenerative therapies for its wound-healing properties and accessibility. While its immediate availability is advantageous, repeated harvesting can be burdensome, especially for elderly patients, and the regenerative capacity of SVF declines with donor age. Long-term cryopreservation offers a potential solution by allowing the banking of SVF from younger donors for future use; however, the impact of this process on SVF functionality remains elusive. This study investigates the stemness and wound-healing potential of SVF following prolonged cryopreservation. Methods: SVF cells were isolated from adipose tissue harvested from twelve patients and cryopreserved for either two months (short-term cryopreserved SVF, S-SVF) or 12–13 years (long-term cryopreserved SVF, L-SVF), with six patients in each group. In vitro assays assessed cell viability and stemness, while in vivo assays evaluated wound-healing ability by administering thawed SVF cells from each group to dorsal wounds in immunodeficient mice, compared with a control group. Non-parametric statistical tests analyzed the differences between groups. Results: L-SVF exhibited significantly lower stemness compared to S-SVF. Importantly, the L-SVF group showed significantly improved wound healing compared with the control group, although the wound-healing effect of L-SVF was inferior to that of the S-SVF. Conclusion: This study demonstrated that, despite reduced stemness, L-SVF retains partial wound-healing potential after 12–13 years of cryopreservation. These findings highlight the need for optimized cryopreservation protocols to enhance SVF viability and regenerative capacity for clinical applications.